Sociedade civil e qualificação profissional no Ceará: construção de espaços de participação - Azevedo, Arlete Rebouças (2007)
This study aims at recalling the participation of civil society’s organizations trajectory in the implementation of the Qualification State Plan of Ceara – PEQ/CE, from the perception of social subjects engaged in it. Its background are the economic, social, political, and cultural transformations that are marking society in the last decades, due to the capital’s globalization, the production restructuring and work management, and the redefinition of State’s role and its relationships with society, scaffolded by neoliberalist hegemony. From such perspective, this research analyzes public policies for jobs in Brazil, by focusing the National Plan for the Qualification of Worker, as well as one of its mechanisms of implementation, the Qualification State Plan of Ceara, object of this empirical investigation. This work had four guideline objectives: a) designing the profile of organized civil societies engaged in the implementation of PEQ-CE; b) understanding the determinative reasons in their ingress in PEQ-CE; c) knowing the experience lived by these organizations in the inscription and selection for PEQ-CE; and d) recalling the experience of organized civil societies in the performance of actions of professional qualification, within such Plan. The methodological procedure comprehended documental and bibliographic studies and qualitative field research, in order to recognize the social experience of the varied subjects engaged in the implementation of PEQ-CE in their relation with the object under investigation. The result of this empirical study shows, from the perception of the varied social subjects involved, the importance of civil society in the Qualification State Plan of Ceara, and in the State Work Council, as mediation between the population’s demands and the governmental programs, as well as in the creation of public spaces of representation and negotiation of people’ interests, in order to inscribe it in the public agenda.